Trends in lifetime risk and years of potential life lost from diabetes in the United States, 1997–2018 - Koyama, Alain K.; Cheng, Yiling J.; Brinks, Ralph; Xie, Hui; Gregg, Edward W.; Hoyer, Annika; Pavkov, Meda E.; Imperatore, Giuseppina (PloS one, 2022)
Both incidence and mortality of diagnosed diabetes have decreased over the past decade. However, the impact of these changes on key metrics of diabetes burden-lifetime risk (LR), years of potential life lost (YPLL), and years spent with diabetes-is unknown. We used data from 653,811 adults aged ≥18 years from the National Health Interview Survey, a cross-sectional sample of the civilian non-institutionalized population in the United States. LR, YPLL, and years spent with diabetes were estimated from age 18 to 84 by survey period (1997-1999, 2000-2004, 2005-2009, 2010-2014, 2015-2018). The age-specific incidence of diagnosed diabetes and mortality were estimated using Poisson regression. A multistate difference equation accounting for competing risks was used to model each metric. LR and years spent with diabetes initially increased then decreased over the most recent time periods. LR for adults at age 20 increased from 31.7% (95% CI: 31.2-32.1%) in 1997-1999 to 40.7% (40.2-41.1%) in 2005-2009, then decreased to 32.8% (32.4-33.2%) in 2015-2018. Both LR and years spent with diabetes were markedly higher among adults of non-Hispanic Black, Hispanic, and other races compared to non-Hispanic Whites. YPLL significantly decreased over the study period, with the estimated YPLL due to diabetes for an adult aged 20 decreasing from 8.9 (8.7-9.1) in 1997-1999 to 6.2 (6.1-6.4) in 2015-2018 (p = 0.02). In the United States, diabetes burden is declining, but disparities by race/ethnicity remain. LR remains high with approximately one-third of adults estimated to develop diabetes during their lifetime.